Predicting Response to Immunotherapy by Evaluating Tumors, Lymphoid Cell-Rich Organs, and Immune-Related Adverse Events Using FDG-PET/CT. (April 2019) - Nobashi, Tomomi; Baratto, Lucia; Reddy, Sunil A.; Srinivas, Sandhya; Toriihara, Akira; Hatami, Negin; Yohannan, Thomas K.; Mittra, Erik
Abstract : Purpose: To investigate whether the evaluation of tumors, lymphoid cell-rich organs, and immune-related adverse events (IRAE) with 18 F-FDG PET/CT can predict the efficacy and outcome of immunotherapy. Methods: Forty patients who underwent 18 F-FDG-PET/CT scans before and after therapy with immune checkpoint inhibitors from December 2013 to December 2016 were retrospectively enrolled (malignant melanoma, n = 21; malignant lymphoma, n = 11; renal cell carcinoma, n = 8). SUVmax of the baseline and first restaging scans were evaluated in tumors, spleen, bone marrow, thyroid and pituitary glands, and were correlated to best overall response in the first year after therapy; IRAE-affected areas were also evaluated. Results: Interval change between the baseline and first restaging scans showed that patients with a clinical benefit had a significant decrease in tumor parameters ( P < 0.001). All patients with an increase of SUVmax in the thyroid of more than 1.5 (n = 5) on the first restaging scan had a complete response (CR) in 1 year. Patients with CR within 1 year (n = 22) were significantly associated with a favorable long-term outcome ( P = 0.002). Nine patients with IRAE findings had CR at final evaluation. Among IRAE, thyroiditis was seen significantly earlier than arthritis ( P = 0.040). Conclusions: The decrease of tumor parameters at early time-point PET scans was seen in patients with immunotherapy who had clinical benefit within 1 year. PET-detectable IRAE was useful for prediction of a favorable outcome. Early development of thyroiditis may particularly represent an early response indicator to immunotherapy.